DESIGN AND CONSTRUCTION OF A GREENHOUSE FOR VEGETABLE DRYING WITH WIND-DRIVEN TURBO VENTILATOR - Abubakar R.A. (International Journal of Engineering Technologies and Management Research, 2025)
This study evaluates the performance of a greenhouse vegetable dryer integrated with a wind-driven turbo ventilator, developed to enhance natural convection and improve the drying process through renewable energy utilization. The design targets small-scale farmers in remote or off-grid are-as, where access to electricity and mechanical drying systems is limited or non-existent. The experi-mental setup involved drying freshly harvested leafy vegetables, which had an initial moisture content of approximately 80%. The test was conducted over a continuous 10-hour period under clear sunlight and moderate natural wind conditions. Key performance parameters—including internal and ambient temperatures, relative humidity, and vegetable moisture content—were systematically measured at two-hour intervals. The results revealed a consistent increase in internal temperature within the dryer, peaking at 49°C, which significantly exceeded the maximum ambient temperature of 33°C. This thermal gain was attributed to the greenhouse effect and the enhanced air circulation enabled by the wind-powered ventilator. Relative humidity within the drying chamber ranged from 55% to 62%, establishing an optimal environment for moisture evaporation. At the end of the drying cycle, the final moisture con-tent of the vegetables was reduced to 15%, marking a 65% total reduction. Compared to conventional passive solar dryers documented in the literature, this system demonstrated improved drying efficiency while maintaining simplicity and requiring no external power. Its performance aligns well with semi-passive systems and even rivals some electrically assisted dryers in efficiency. The ventilator played a key role by preventing internal heat saturation and promoting consistent airflow. Overall, the system offers a promising, cost-effective, and sustainable approach for post-harvest preservation of perishable crops in resource-limited settings.